2022
DOI: 10.3390/ani12182449
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitogenomes of Polypedates Tree Frogs Unveil Gene Rearrangement and Concerted Evolution within Rhacophoridae

Abstract: New developments in sequencing technology and nucleotide analysis have allowed us to make great advances in reconstructing anuran phylogeny. As a clade of representative amphibians that have radiated from aquatic to arboreal habitats, our understanding of the systematic status and molecular biology of rhacophorid tree frogs is still limited. We determined two new mitogenomes for the genus Polypedates (Rhacophoridae): P. impresus and P. mutus. We conducted comparative and phylogenetic analyses using our data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 134 publications
1
3
0
Order By: Relevance
“…In the current study, the phylogenetic tree showed the pairs of P. mutus and P. braueri versus P. megacephalus and P. impresus formed separate decisive sister groups. This topology was consistent with that published previously in other studies [ 21 , 86 , 87 ]. Past studies revealed that the P. leucomystax complex was considered to be composed of seven highly supported clades [ 2 , 87 , 88 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, the phylogenetic tree showed the pairs of P. mutus and P. braueri versus P. megacephalus and P. impresus formed separate decisive sister groups. This topology was consistent with that published previously in other studies [ 21 , 86 , 87 ]. Past studies revealed that the P. leucomystax complex was considered to be composed of seven highly supported clades [ 2 , 87 , 88 ].…”
Section: Discussionsupporting
confidence: 93%
“…Gene rearrangement is a frequent phenomenon in tree frogs and can be explained by the tandem duplication–random loss (TDRL) model [ 16 ] and the slipped-strand mispairing model [ 17 ]. Among the known species of tree frogs, mitochondrial ND5 gene rearrangements are classified into the following two types: (1) those in which the ND5 gene is shifted from between ND4 and ND6 genes to between the CR and LTPF gene cluster ( Buergeria buergeri [ 18 ], Zhangixalus dennysi [ 19 ]), and (2) those in which the ND5 gene is translocated between the two CRs ( Zhangixalus schlegelii [ 20 ], P. impresus [ 21 ], Polypedates mutus [ 21 ], Polypedates braueri [ 22 ]). The mitogenome of P. megacephalus was initially sequenced by Zhang et al, revealing a 16,473 bp genome lacking the ND5 gene and the ATP8 gene [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene rearrangement is a frequent phenomenon in tree frogs and can be explained by the tandem duplication-random loss (TDRL) model [16] and the slipped-strand mispairing model [17]. Among the known species of tree frogs, mitochondrial ND5 gene rearrangements are classified into the following two types: (1) those in which the ND5 gene is shifted from between ND4 and ND6 genes to between the CR and LTPF gene cluster (Buergeria buergeri [18], Zhangixalus dennysi [19]), and (2) those in which the ND5 gene is translocated between the two CRs (Zhangixalus schlegelii [20], P. impresus [21], Polypedates mutus [21], Polypedates braueri [22]). The mitogenome of P. megacephalus was initially sequenced by Zhang et al, revealing a 16,473 bp genome lacking the ND5 gene and the ATP8 gene [23].…”
Section: Introductionmentioning
confidence: 99%